Implementasi Digital Marketing dan Technopreneur dalam Meningkatkan Kinerja Keuangan Pada UMKM Kota Medan - Rahma; Rahmadani, Rahmadani; Simanungkalit, Erwinsyah; Zuardi, Muhammad; Binti Jaafar, Rosmawati (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
This study will provide an overview of how the use of digital marketing and technopreneurs affects the financial performance of MSMEs. Another important thing is for MSMEs to have a technopreneur mentality. The purpose of using digital marketing is to increase market share in productive partners if applied as a technology in MSMEs. The long-term goal of this study is to provide literacy to MSMEs on how to develop a technology-based marketing system that is easy and has an impact on financial performance. This study is a qualitative study by analyzing data using NVivo 15 software. Data collection techniques were carried out using interviews, observations, and documentation. The results of this study indicate that the application of digital marketing and technopreneurs has an impact on the Company's performance, including financial performance. A technology-based marketing system is right to be applied to the Beranda Street House MSME, which is an MSME in the food and beverage sector.